2010
DOI: 10.1158/0008-5472.can-09-3800
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of Centrosome Homeostasis and DNA Repair Is Intact in MCF-7 and Disrupted in MDA-MB 231 Breast Cancer Cells

Abstract: When cells encounter substantial DNA damage, critical cell cycle events are halted while DNA repair mechanisms are activated to restore genome integrity. Genomic integrity also depends on proper assembly and function of the bipolar mitotic spindle, which is required for equal chromosome segregation. Failure to execute either of these processes leads to genomic instability, aging, and cancer. Here, we show that following DNA damage in the breast cancer cell line MCF-7, the centrosome protein centrin2 moves from… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…It thus seems likely that the nuclear localisation of centrin2 is an important determinant of NER efficiency. Several studies have indicated that this localisation depends on centrin2 interacting directly with XPC [36,56,57]. A role for centrin2 SUMOylation in regulating this interaction and thus, the movement of centrin2 into the nucleus for NER, was suggested from RNAi experiments that disrupted the SUMOylation machinery [58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It thus seems likely that the nuclear localisation of centrin2 is an important determinant of NER efficiency. Several studies have indicated that this localisation depends on centrin2 interacting directly with XPC [36,56,57]. A role for centrin2 SUMOylation in regulating this interaction and thus, the movement of centrin2 into the nucleus for NER, was suggested from RNAi experiments that disrupted the SUMOylation machinery [58].…”
Section: Discussionmentioning
confidence: 99%
“…The role played by centrin2 in NER is unclear: in vitro NER can be carried out in its absence, although it increases NER activity somewhat [3235]. Nevertheless, centrin2 moves to the nucleus after UV irradiation in an XPC-dependent manner and is required for efficient repair of UV-induced DNA lesions in both human and chicken cells [25,36]. …”
Section: Introductionmentioning
confidence: 99%
“…Cells were centrifuged again at 1,000 × g , resuspended in 1 ml of PI/RNase solution (40 µg/ml PI and 50 µg/ml RNase in PBS), and incubated in PI/RNase solution at 4°C overnight before analysis. FACS analysis was performed in PI/RNase solution on a Becton Dickinson FACScan [Acu et al, 2010]. …”
Section: Methodsmentioning
confidence: 99%
“…Recent studies of centrin2 in breast cancer cell lines MCF-7 suggest a possible link between centrin function at the nucleus and the centrosomes (Acu et al 2010). Upon DNA damage, centrin2 is recruited to the nucleus for NER function in an XPC-dependent manner, leaving less centrin present at the centrosomes and thus causing cell cycle arrest, whereas in XPC-deficient MDA-MB231 and XPC-null fibroblast cells, centrin lost the ability to relocate from the centrosomes to the nucleus and centrosome amplification occurred following DNA damage.…”
Section: Functional Diversity Of Centrinsmentioning
confidence: 99%